Neutrophil-to-lymphocyte ratio as a predictor for early mortality in older patients requiring hemodialysis; insights for hemodialysis access planning - Hyo Kee Kim; Heungman Jun; Sun-Young Ko (BMC Nephrology)
Abstract Introduction The 2019 Kidney Disease Outcome Quality Initiative guidelines emphasize the importance of selecting dialysis based on the life expectancy of the patient. However, it is difficult to predict the life expectancy of a patient during arteriovenous fistula creation. We investigated whether neutrophil-to-lymphocyte, monocyte-to-lymphocyte, and platelet-to-lymphocyte ratios measured before dialysis could predict mortality. Materials and methods Between January 2016 and December 2020, we retrospectively analyzed electronic medical records of 448 patients aged ≥ 70 years undergoing first-time arteriovenous access surgery at three tertiary care hospitals, all of whom had not received prior dialysis treatment. Only patients undergoing blood tests on the day before surgery were included in the analysis. Patients who died within one year after surgery were included in the non-survival group, while those who died after one year were included in the survival group. Results Patients were categorized into non-survival (n = 52) and survival (n = 396) groups. Multivariate analysis for one-year mortality revealed that the preoperative neutrophil-to-lymphocyte ratio demonstrated a 1.15 hazard ratio ( p < 0.001 ). Also, cancer (HR 2.50, p = 0.02) and peripheral arterial disease (HR 4.62, p < 0.001) were risk factor for one-year mortality. The preoperative platelet-to-lymphocyte and monocyte-to-lymphocyte ratios were not identified as one-year mortality risk factors. In the total mortality multivariate analysis, monocyte-to-lymphocyte ratios were one of the risk factors (HR 2.74, p < 0.007). Conclusion The neutrophil-to-lymphocyte ratio was a risk factor associated with one-year mortality in patients aged ≥ 70 years. However, further research is required to determine whether these can be used for predictive purposes.